“La Pedagogía Crítica en el aula y su Impacto en el Aprendizaje de los Estudiantes” - Calvopiña Cerna, Miriam Jessenia (2024)
Currently, the educational field has been undergoing an evolution as well as some problems into the educational reality. For this reason, this research project is focused on the knowledge and applicability of Critical Pedagogy in the learning process of students. Through a bibliographic review, has been confirmed, that mainly traditional pedagogy had been used in educational institutions for learning. However, Critical Pedagogy is becoming in more relevant, as it allows to students to develop their abilities and capabilities by promoting reasoning, analysis, participation and critical capacity. In this context, the aim of the research is to set up the incidence of Critical Pedagogy in the classroom and its impact on student learning. To this, a documentary investigation has been conducted the documentary using the analysis technique, this has made it possible to collect important information about the problem raised. It has been concluded that the application of the Critical Pedagogy that helps the development of reflective and critical thinking in students, giving them the opportunity to strengthen their people skills. This is beneficial for the students’ development as inside and outside the classroom, and promote to the progress to a more just, fair and, democratic society.